Examining Race as a Predictor and Moderator of Treatment Outcomes for Binge-Eating Disorder: Analysis of Aggregated Randomized Controlled Trials - Lydecker, Janet A. (J Consult Clin Psychol, 2019)
OBJECTIVE: To examine whether race predicted or moderated response to treatments for binge-eating disorder (BED). METHOD: Participants were 592 adults (n=113 Black; n=479 White) with DSM-IV-defined BED who participated in randomized controlled trials (RCTs) at one medical center. Data were aggregated from RCTs for BED testing cognitive-behavioral therapy, behavioral weight loss, multi-modal treatment, and/or control conditions. Participants had weight and height measured and were assessed using established interviews and self-report measures at baseline, throughout treatment, and post-treatment. RESULTS: Race did not significantly moderate treatment outcomes. Mixed models revealed a main effect of race: Black participants had fewer binge-eating episodes and lower depression than White participants across time points. Race also had a main effect in generalized estimating equations with a significantly greater proportion of Black participants achieving binge-eating remission than White participants. Race did not predict percent weight loss, but a significantly lower proportion of Black participants attained 5% weight loss than White participants. Race did not significantly predict global eating-disorder severity. CONCLUSION: Despite disparities in treatment-seeking reported in epidemiological and RCT studies, Black individuals appear to have comparable or better treatment outcomes in BED treatment research compared with White individuals, except they were less likely to attain 5% weight loss at post-treatment. This suggests that disseminating evidence-based treatments for BED among diverse populations holds promise and treatments may not require further adaptation prior to dissemination. Implementation research is needed to test treatment effectiveness across diverse providers, settings, and patient groups to improve understanding of potential predictors and moderators.